A Retrospective Comparative Evaluation of Selected Blood Cell Ratios, Acute Phase Proteins, and Leukocyte Changes Suggestive of Inflammation in Cats - Giulia Donato; Maria Grazia Pennisi; Maria Flaminia Persichetti; Joy Archer; Marisa Masucci (Animals, 2023)
Neutrophil-to-lymphocyte (NLR), monocyte-to-lymphocyte (MLR), and platelet-to-lymphocyte (PLR) ratios have been proposed as diagnostic and prognostic markers for neoplastic and inflammatory diseases in dogs and cats. The aim of this retrospective preliminary study was to evaluate the relationship between these ratios and markers of inflammation routinely measured in cats. A total of 275 cats were enrolled. Complete blood count, serum amyloid A (SAA), albumin, globulin, and albumin-to-globulin ratio (AGR) data were analyzed, as well as the presence of leukocyte alterations considered suggestive of inflammation (LAI: neutrophils left shift, toxic neutrophils, and reactive lymphocytes) evaluated in blood smears. The NLR and MLR correlated positively with SAA and globulins and negatively with albumin and AGR. Higher NLR and MLR were found in cats with increased SAA and globulins and decreased albumin and AGR. The PLR correlated negatively with albumin and AGR. A higher PLR was found in cats with hypoalbuminemia. Cats with LAI had higher NLR, MLR, and PLR. In cats with no changes in parameters indicative of inflammation, 11.25, 0.42, and 528.3 were identified as upper limits for NLR, MLR, and PLR, respectively. In conclusion, the NLR, MLR, and PLR act as good inflammatory markers easily evaluated by routine hematology.